Cost-effectiveness analysis of eight first-line treatments for metastatic hormone-sensitive prostate cancer in China - Han, Zhou; Xi, Youli; Hu, Jian; Wang, Ye; Ni, Huanyu (Frontiers in Pharmacology, 2025)
BackgroundThe treatment of metastatic hormone-sensitive prostate cancer (mHSPC) has shifted from androgen deprivation therapy (ADT) alone to doublet or triplet regimens building on ADT. However, the cost-effectiveness analysis of first-line treatments for mHSPC in China is uncertain. This study aims to perform a 10-year horizon health economic evaluation to comparatively analyze the cost-effectiveness of eight treatment regimens for mHSPC from the perspective of China’s healthcare system, including (1) ADT alone and ADT plus one of the following: (2) docetaxel, (3) abiraterone, (4) apalutamide, (5) enzalutamide, (6) rezvilutamide, (7) darolutamide and docetaxel, (8) abiraterone and docetaxel.MethodsPartitioned survival model was developed to evaluate the cost-effectiveness of eight first-line treatment regimens for mHSPC. Drug costs were primarily extracted from pharmaceutical databases. The key outcomes were quality adjusted life years (QALYs), costs and the incremental cost-effectiveness ratio (ICER). Willingness-to-pay (WTP) threshold was set as three-time China’s gross domestic product (GDP) per capita (US$38,024) per QALY.ResultsFor costs, the 10-year cost estimates ranged from US$120,844 for ADT alone to US$216,294 for darolutamide plus ADT with docetaxel. For clinical effectiveness, enzalutamide plus ADT yielded the highest QALYs (4.55), while ADT alone gained lowest QALYs (3.01). For cost-effectiveness, the three treatment regimens of ADT alone, abiraterone plus ADT and enzalutamide plus ADT constituted the cost-effectiveness frontier. Abiraterone plus ADT emerged as the most cost-effective strategy, indicative of an ICER of US$17437.16 per QALY, substantially below WTP threshold.ConclusionAbiraterone plus ADT was likely to be cost-effective for mHSPC treatment at a WTP threshold of three-time per capita GDP per QALY.